Targeting CLDN18.2 in cancers of the gastrointestinal tract: New drugs and new indications - Chen, Jinxia; Xu, Zhiyuan; Hu, Can; Zhang, Shengjie; Zi, Mengli; Yuan, Li; Cheng, Xiangdong (Frontiers in Oncology, 2023)
Cancers of the gastrointestinal (GI) tract greatly contribute to the global cancer burden and cancer-related death. Claudin-18.2(CLDN18.2), a transmembrane protein, is a major component of tight junctions and plays an important role in the maintenance of barrier function. Its characteristic widespread expression in tumour tissues and its exposed extracellular loops make it an ideal target for researchers to develop targeted strategies and immunotherapies for cancers of the GI tract. In the present review, we focus on the expression pattern of CLDN18.2 and its clinical significance in GI cancer. We also discuss the tumour-promoting and/or tumour-inhibiting functions of CLDN18.2, the mechanisms regulating its expression, and the current progress regarding the development of drugs targeting CLDN18.2 in clinical research.